1979
DOI: 10.1115/1.3448985
|View full text |Cite
|
Sign up to set email alerts
|

Drag on an Oscillating Airfoil in a Fluctuating Free Stream

Abstract: An analytical study is presented regarding the unsteady skin friction drag of an oscillating airfoil exposed to a fluctuating free stream speed. Both laminar and turbulent conditions are covered in the analysis. The unsteady potential flow pressure and velocity distributions required for the subsequent boundary layer analysis are obtained by an approximate development. The time-dependent boundary layer is solved by a finite difference scheme. It was found that depending on the values of the phase difference be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Although some experimental research regarding unsteady inflow effects on pitching airfoils has been performed, much less computational work has been done in this area due to the difficulty of coupling nonuniform inflow conditions with a dynamic pitching motion in computational models. In the 1970s, Pierce et al [2] and Kottapalli and Pierce [20] performed experiments on pitching helicopter blades with cyclic inflow conditions, showing that these inflow conditions affected the forces and moments on the blade with varying magnitudes dependent upon the phase difference between the airfoil oscillation and inflow velocity oscillation. A similar study by Shi and Ming [5,6] investigated a pitching delta wing, for improvements in the design of supermaneuverable aircraft.…”
mentioning
confidence: 99%
“…Although some experimental research regarding unsteady inflow effects on pitching airfoils has been performed, much less computational work has been done in this area due to the difficulty of coupling nonuniform inflow conditions with a dynamic pitching motion in computational models. In the 1970s, Pierce et al [2] and Kottapalli and Pierce [20] performed experiments on pitching helicopter blades with cyclic inflow conditions, showing that these inflow conditions affected the forces and moments on the blade with varying magnitudes dependent upon the phase difference between the airfoil oscillation and inflow velocity oscillation. A similar study by Shi and Ming [5,6] investigated a pitching delta wing, for improvements in the design of supermaneuverable aircraft.…”
mentioning
confidence: 99%
“…They also found that the dynamic stall starts at a later time at high angle of attacks due to delayed formation and detachment of the dynamic stall vortex. Several other previous researchers [15][16][17][18][19][20][21] have demostrated that the impact of unsteady inflow on aerodynamic loads is also applicable to helicopters and maneuverable wings working in the environment with freestream velocity fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…At the present time, some experimental research has been performed to examine the effects of unsteady inflow on pitching airfoils, while a much smaller amount of computational work has been done in this area. In the 1970's Pierce et al 2 and Kottapalli et al 15 performed experiments on pitching helicopter blades using a gust generator to produce periodic inflow conditions. Their results show that the varying freestream velocity affects the pitching moment and drag experienced by the blade, and that the magnitudes of the forces and moment change depending on the phase difference between the airfoil oscillation and inflow velocity oscillation.…”
Section: Introductionmentioning
confidence: 99%